TINGKAT KEBERHASILAN INSEMINASI BUATAN PADA TERNAK BABI (Sus vittatus) DI UPTD BALAI PEMBIBITAN TERNAK PROVINSI PAPUA DI KAMPUNG HARAPAN DISTRIK SENTANI TIMUR - Merpati; Kondong, Dortje Janet (STIPER Santo Thomas Aquinas Jayapura, 2022)
This study aims to determine the success rate of the artificial insemination program in pigs at the UPTD Livestock Breeding Center in Harapan Village, East Sentani District, Jayapura Regency. The research method used is a survey method with interview techniques using questionnaires to obtain primary data, as well as conducting observations to see the condition of pigs that have been artificially inseminated. The variables observed in this study included: (1) the number of inseminated females; (2) the number of pregnant females; (3) The number of inseminated females and normal offspring; (4) The number of straws used. The results of the study obtained the number of Service Per Conception (S/C) = 1.3; Conception Rate (CR) = 83% and Calving Rate (C/R) = 77%. Conclusion: the implementation of IB at the UPTD of the Kampung Harapan Livestock Breeding Center can be said to be quite successful.